2018
DOI: 10.3389/fnana.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ascending Projections From the Male Rat Caudal Nucleus of the Tractus Solitarius: An Interface Between Local Microcircuits and Global Macrocircuits

Abstract: To integrate and broadcast neural information, local microcircuits and global macrocircuits interact within certain specific nuclei of the central nervous system. The structural and functional architecture of this interaction was determined for the caudal nucleus of the tractus solitarius (NTS) at the level of the area postrema (AP), a relay station of peripheral viscerosensory information that is processed and conveyed to brain regions concerned with autonomic-affective and other interoceptive reflexive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 80 publications
3
31
0
Order By: Relevance
“…Cre-conditional tracing eliminates these confounds because only neurons that express Hsd11b2 at or after the time of AAV injection can produce the genetically encoded tracer, so labeled axons emit exclusively from HSD2 neurons. That HSD2 neurons provide minimal (or no) projections within the NTS places them in a previously described class of NTS neurons that lack local, axon-collateral projections (Kawai and Senba, 1996; Kawai, 2018), with important functional implications for HSD2 neurons and, by extension, aldosterone. That is, whether or not HSD2 neurons influence sodium taste detection or any autonomic reflexes, it is highly unlikely that they exert such influence directly within the brain’s first-order gustatory and viscerosensory nucleus, the NTS.…”
Section: Discussionmentioning
confidence: 93%
“…Cre-conditional tracing eliminates these confounds because only neurons that express Hsd11b2 at or after the time of AAV injection can produce the genetically encoded tracer, so labeled axons emit exclusively from HSD2 neurons. That HSD2 neurons provide minimal (or no) projections within the NTS places them in a previously described class of NTS neurons that lack local, axon-collateral projections (Kawai and Senba, 1996; Kawai, 2018), with important functional implications for HSD2 neurons and, by extension, aldosterone. That is, whether or not HSD2 neurons influence sodium taste detection or any autonomic reflexes, it is highly unlikely that they exert such influence directly within the brain’s first-order gustatory and viscerosensory nucleus, the NTS.…”
Section: Discussionmentioning
confidence: 93%
“…However, all or a portion of the two oscillator activities would vary according to consciousness level or quality (such as attention or learning) of animals or individuals. These two brainstem oscillators seem to orchestrate neuronal activities of not only the VC but also other wide-ranging brainstem neuronal groups, including catecholaminergic, cholinergic, and serotonergic systems (Kawai, 2018), through a phase-phase coupling mechanism, to perform specific physiological functions. The oscillatory synchrony and the ascending macrocircuits (Kawai, 2018) could represent functional and anatomic substrates for the presumed ascending reticular activating system including the bulbar reticular formation (Moruzzi and Magoun, 1949).…”
Section: Resultsmentioning
confidence: 99%
“…However, a neuronal population microenvironment close to an electrode tip differs extremely from other brain areas depending on the neuronal size and density. The VC consists mostly of small cells (Yoshioka et al, 2006; Negishi and Kawai, 2011); VC cell size (~10 μm in diameter) and density (~2.0 × 10 5 /mm 3 in numerical density) would make for a far more numerous and denser cell population near the recording electrode tip than in the cerebral cortex or hippocampus (Buzsaki, 2006; Kawai, 2018), allowing any unusual neuronal activity profiles to be revealed, as demonstrated in the present study. That is, recorded neuronal activities in the VC contained not only typical single- or multi-unit spikes but also longer duration LFP-like waves, and in occasion, high-amplitude potential waves (mostly polyphasic), possibly due to a reflection of synchronized activity produced by the spatially compact neuronal population (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axonal tracing studies have identified output projections from the NTS to a variety of regions in the upper brainstem and forebrain (Gasparini et al, 2019; Geerling & Loewy, 2006b; Herbert et al, 1990; Kawai, 2018; Ricardo & Koh, 1978; Ter Horst, de Boer, Luiten, & van Willigen, 1989). Prominent targets include the parabrachial nucleus (Herbert et al, 1990; Herbert & Saper, 1990), ventrolateral periaqueductal gray matter (Kawai, 2018), hypothalamus (Ter Horst et al, 1989), CeA, and ventrolateral BST (Bienkowski & Rinaman, 2013; Geerling & Loewy, 2006b; Ricardo & Koh, 1978; Shin et al, 2008; Sofroniew, 1983; Terenzi & Ingram, 1995).…”
Section: Discussionmentioning
confidence: 99%